2022
DOI: 10.3390/ijerph191912201
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Prevention for Survivors: Incidence of Second Primary Cancers and Sex Differences—A Population-Based Study from an Italian Cancer Registry

Abstract: Background: The number of cancer survivors continues to increase, thanks to advances in cancer diagnosis and treatment. Unfortunately, the incidence of a second primary cancer (SPC) is also increasing, but limited studies reporting incidence data are available regarding multiple cancers. This study presents our observations on multiple primary malignant cancers, the associations between sites, and the inherent sex differences. Patients and methods: We report the data, disaggregated by sex, concerning the SPCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
1
6
1
Order By: Relevance
“…Among PM cases collected in the RML, a diagnosis of SPC was reported in 15% of patients. This percentage is far higher than previously reported in other Italian studies on the general cancer population at the national and regional levels [ 28 , 29 ], probably due to different methodologies in retrieving SPC data. In our study, the presence of an SPC was retrieved from the medical records at the time of inclusion in the registry database and also asked about during the interview carried out to collect asbestos exposure history.…”
Section: Discussioncontrasting
confidence: 70%
“…Among PM cases collected in the RML, a diagnosis of SPC was reported in 15% of patients. This percentage is far higher than previously reported in other Italian studies on the general cancer population at the national and regional levels [ 28 , 29 ], probably due to different methodologies in retrieving SPC data. In our study, the presence of an SPC was retrieved from the medical records at the time of inclusion in the registry database and also asked about during the interview carried out to collect asbestos exposure history.…”
Section: Discussioncontrasting
confidence: 70%
“…Another strength of this study is that it was based on the SEER database, one of the world's largest cancer databases, covering approximately 30% of the US population. As mentioned earlier, a study based on the Italian cancer registry found a higher risk of SPC among males 5 . A German cancer registry study evaluating the risk of SPC among colorectal PC had similar findings 33 .…”
Section: Discussionsupporting
confidence: 61%
“…In particular, males over 70 had an SPC incidence rate 3.25 times that of females. While for those younger than 50, the SPC incidence rate for females was twice that of males 5 . In 2020, a global study found that nearly half of the newly diagnosed cancer cases were in the elderly, aged 65 or above 6 .…”
Section: Introductionmentioning
confidence: 99%
“…They similarly observed an increase in risk for individuals with a younger age at first cancer diagnosis. An Italian study of 165,179 FPC and 11,348 SPC found substantial sex-differences in the locations of the SPC [9]. This study concluded, among other things, that the development of cancer screening and surveillance plans should be considered based on the risk of common SPC sites [9].…”
Section: Discussionmentioning
confidence: 92%
“…In Canada, it is not currently known the rate at which subsequent cancers occur among adult cancer survivors and the relative risk when compared to that observed in the general population. Several studies outside Canada have investigated the risk of SPC development [6][7][8][9][10], however, to our knowledge, there are no Canadian data comprehensively characterizing the landscape of SPC risk. The goal of this study was to estimate the risk of developing a SPC among adult cancer survivors in Alberta, Canada, with an emphasis on screen-detectable cancers.…”
Section: Introductionmentioning
confidence: 99%